SOCIAL ROLE RELATIONSHIP TO DEPRESSION IN THE ELDERLY IN CANDIMULYO VILLAGE JOMBANG SUBDISTRICT - niki Natalia (Jurnal EduHealth, 2020)
Depression is one of the disorders in the nature of feelings (affective, mood) characterized by depression, sadness, lethargy, loss of passion, no spirit in the self. The elderly will be more susceptible to depression if in the elderly are less able to socialize with the surrounding environment against the decline in social function. The purpose of this study is to find out the relationship of social role to depression in the elderly in Candimulyo Village, Jombang Regency. Research design is correlation analytics. The population in this study is elderly in Candimulyo Village, Jombang Regency. In this study, the sampling technique used is Simple Random Sampling. Data collection using questionnaires by processing data using editing, cooding scoring, tabulating with spearman rank statistical tests. The results showed that 50 respondents were known that respondents who experienced bad social roles as many as 19 (38.0%), respondents who experienced moderate social roles as much as (30.0%), respondents who experienced good social roles as much as (2.0%). Respondents who experienced a level of major depression as much as (48.0 %), moderate depression level as much as (40%), severe depression level once (8.0%) and mild depression rate (4.0%). The conclusion of this study there is a relationship between the social role of depression in the elderly in Candimulyo Village, Jombang Regency.